Corporate risk reporting: a study of risk management disclosure between sectors in annual reports of Malaysian public listed company / Rozaida Abu Shari - Abu Shari, Rozaida (2011)
Risk disclosure has received considerable interest and attention in recent times especially by the regulators such as Bursa Malaysia Listing Requirement, Malaysian Corporate Governance and Securities Commissions. The objective of this research is to examine the level of risk disclosure in annual reports of the companies in Malaysia. This research is empirically examines the firms' characteristics that influence the level of risk disclosure in the annual reports. The firms' characteristics include the firm size, profitability, leverage, sector type, presence of a risk committee and board composition. The level of risk disclosure is determined by the types of risk which are environmental risks, operational risks and strategic risks. In addition the research examines the association between risk management disclosures and firms' characteristics. The data was sought, collected and analysed from a sample of 121 companies annual reports drawn from the company's World Wide Web (www) and published annual reports in year 2009. Content analysis was applied and risk disclosure in the annual report was measured according to the number of sentences disclosed. Risk disclosure sentences were classified under category of risks and nature of the risks disclosed. This study found that most of the companies in Malaysia disclose risks in their annual report but at a lower level. Even though all the companies have experienced in 2007 and 2008 the financial crisis which had led to some companies to fail and to exit from the market, the willingness of the directors to disclose their risk reporting as a voluntary disclosure in annual reports is however unfortunately still low. In particular, the new regulation by the regulators had failed to attract the directors to be more transparent and therefore provide valuable information to the stakeholders. The findings also reveal that only SIZE of the company has negative relationship with the level of risk disclosure for companies in Malaysia. Other firm's characteristic are found to be not significant to the relationship. This suggests that the willingness of the directors to disclose risk information in their annual reports does not depend on the characteristics discussed. This may due to the fact that risk disclosure is on voluntary basis and most of the companies in Malaysia are family-owned. Overall the analysis suggests that Malaysian companies do disclosed risk information in the annual reports but the usefulness of this disclosure is however very limited. Further longitudinal research is recommended in order to enable a meaningful comparison between the years.